2022
DOI: 10.1073/pnas.2122716119
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils activated by membrane attack complexes increase the permeability of melanoma blood vessels

Abstract: The microenvironment of malignant melanomas defines the properties of tumor blood vessels and regulates infiltration and vascular dissemination of immune and cancer cells, respectively. Previous research in other cancer entities suggested the complement system as an essential part of the tumor microenvironment. Here, we confirm activation of the complement system in samples of melanoma patients and murine melanomas. We identified the tumor endothelium as the starting point of the complement cascade. Generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…The arachidonic acid pathway is a metabolic process that plays a key role in carcinogenesis, and its enzymes are emerging as novel targets for cancer prevention and therapy ( Yarla et al, 2016 ). Simultaneously weakening the complement system and the coagulation cascade seems to be a prudent treatment for cancer patients ( Liu et al, 2022b ). The pyrimidine pathway contributes to cancer mechanisms ( Weber, 1983 ).…”
Section: Discussionmentioning
confidence: 99%
“…The arachidonic acid pathway is a metabolic process that plays a key role in carcinogenesis, and its enzymes are emerging as novel targets for cancer prevention and therapy ( Yarla et al, 2016 ). Simultaneously weakening the complement system and the coagulation cascade seems to be a prudent treatment for cancer patients ( Liu et al, 2022b ). The pyrimidine pathway contributes to cancer mechanisms ( Weber, 1983 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated NETs are present in many lung diseases including Cystic Fibrosis (CF), non-CF bronchiectasis, asthma and COPD (27)(28)(29)(30). We and others have demonstrated that NETs can disrupt barrier function of the epithelium and endothelium, a key mechanism of NET-induced pathogenesis in the lung (10,31). NETs are complex structures with over 100 proteins, many of which are immunomodulatory, so defining NET concentrations is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer endothelium functions as a starting point of the complement cascade. C5a promotes to recruit neutrophils 89 . After contacting with the vascular endothelium, neutrophils are activated via complement membrane attack complexes (MACs), with subsequent generation of NETs.…”
Section: Netosis In Cancer Metastasismentioning
confidence: 99%
“…C5a promotes to recruit neutrophils. 89 After contacting with the vascular endothelium, neutrophils are activated via complement membrane attack complexes (MACs), with subsequent generation of NETs. Behind the wall of blood vessels, NETs open the endothelial barriers, with enhancement in vascular leakage, resulting in the access of cancer cells to the circulating system and systemic dissemination.…”
Section: Extravasationmentioning
confidence: 99%